Psychometric characteristics of the Torrance test for Creative thinking (verbal image) among a sample of basic Education students (second cycle) in the city of Daraa (Damascus University Journal of educational and Psychologyical sciences, 2022)
The research aims to study the psychometric properties of the Torrance test for creative thinking (verbal image) among a sample of basic education Students (second cycle) in the city of Daraa.Various methods were used to study the validity and reliability of the test. The Sample consisted of (403) male and female students, and it included (174) Male and (229) female students.  The results showed good evidence for the validity of the test by examining the Apparent validity of the test and its validity in terms of the test of extreme Groups, and the structural validity of the test, as well as the results showed Good indicators of test reliability by verifying the repetition stability, half-Segmentation stability, alpha-Cronbach stability   and internal consistency, as the results showed. The absence of a statistically significant difference in Creative skills and the overall score according to the gender variabl.On this, the research concluded that the Torrance Test for Creative Thinking (verbal image) has good psychometric properties in the Syrian environment, and its suitability for use in it is within the limits of the research sample
Keywords: psychometric properties; creative thinking